Enhancing Teaching: The Crucial Role of Effective Preparation and Delivery of Lectures - Iryna Hontarenko; Oksana Kovalenko (Educational Challenges)
The article addresses the issue of identifying the most efficient methods for preparing and delivering university lectures. Despite being the oldest instructional approach, lectures remain widely employed in universities worldwide. However, recent pedagogical research by Ukrainian scholars has not fully explored this matter, hindering the development of practical guidelines for instructors aiming to organize and deliver effective lecture courses.